Prototype for Implementing Data Exchange with The FHIR-HL7 Standard in The Personal Health Record Application - Prakosa, Hendri Kurniawan; Ibad, Hasan Nurul; Anwar, Saiful (Intechno Journal : Information Technology Journal, 2024)
Monitoring health is essential for early disease detection, prevention, and managing chronic conditions. Active tracking empowers patients to make informed decisions and adhere to treatments, improving outcomes. However, fragmented medical records across facilities can lead to incomplete information. Integrating records through interoperable systems provides patients and providers with a comprehensive health overview, ensuring continuity, reducing redundancies, and enhancing collaboration. Centralized health data enables better monitoring for patients and more personalized, efficient care from healthcare professionals. This study focuses on developing a prototype for data exchange implementation using the FHIR-HL7 standard in a Personal Health Record (PHR) application. The prototype is tested with selected resources: Patient, Encounter, Observation, and Condition. The data flow involves obtaining patient medical records from an Electronic Health Record (EHR) and displaying them in a Personal Health Record application, ensuring secure access via National Identification Number (NIK) matching as Personal Identification Number. The approach includes mapping FHIR resources to relevant data structures, modifying both EHR and PHR applications to support the data exchange process. The results demonstrate that patient medical records stored in EHR can be accessed by patients through the PHR apps. Specific FHIR resources enable the exchange of various data types: patient demographics using the Patient resource, diagnoses using the Condition resource, and vital signs (e.g., systolic/diastolic blood pressure, weight, height) using the Observation resource. This prototype highlights the feasibility of integrating FHIR-HL7 standards for interoperable health data exchange, enhancing patient engagement and data accessibility.